PEMBANGUNAN PERUMAHAN RAKYAT DALAM PERSPEKTIF MASHLAHAH STUDI KASUS : PERUM PERUMNAS - Bahril D.S (Journal Analytica Islamica, 2016)
This research aims to analyse the construction of reality on development of low cost housing for low income group of the peoples.This study is qualitative research that examines the existence of development of housing for 40 years. The vision and mission of the government is to provide decent and affordable houses for the peoples  of Indonesia. The government founded a public company to realized the vision and mission above. Perusahaan Umum Pembangunan Perumahan Nasional (Perum Perumnas ) established on July 18, 1974. The Perumnas as a the main actors provide a home for the low income group (MBR). The Perumnas established base on non profit oriented as a part of public service from the government. Preface of UUD 1945 declared that, State founded  to make the prosperity for the peoples, such as affordable houses.This concepts is most compatible with Islamic economic principles, to get Falah (Prosperity) through Mashlahah. The problem is still very large of housing shortage (backlog), ie 13.5 million home in 2014. Since the period of 1974-1997, Perumnas has managed to build as many as 455,000 housing units. In carrying out its  activities Perumnas is not intended for profit and in the process of business activities, concepts of Islamic Economics has been run, like antarodin minkum, ta’awun, ad’l, avoiding ihtikar and gharar. During the period 1998 – 2014, there is no longer the concepts above. The government releases home supply to the market. It is up to market forces. Including enacting Perumnas as regular developers are required of seeking profits and no funding from the Government. In this period, Perumnas only capable of building 100,000 housing units. The Government must to restore the role of Perumnas as the main actors provide a home for MBR. The concepts of house development in accordance with the 1945 Constitution and  compatible with the principles of Islamic economics can only executed if the land and housing issue could be controlled by the Government, not left to the market mechanism.